Random laser generation in rhodamine-doped aerogel - De Miranda, Adriana Ramos; Pecoraro, Édison [UNESP]; Lima Ribeiro, Sidney José [UNESP]; Giehl, Júlia Maria; Reijn, Saara-Maarit; Wetter, Niklaus Ursus (Optica Publishing Group, 2013)
Random Laser generation can give valuable information on the structure of diffuse materials. We demonstrate for the first time random laser generation from an aerogel matrix doped with rhodamine 6G. © OSA 2013.